THE TYPES OF MAXIM VIOLATION FOUND IN LUCA MOVIE - Ayu Widiasih; Putu Nur Ayomi; Ida Bagus Gde Nova Winarta (Journal of Education, Linguistics, Literature and Language Teaching, 2022)
The study aimed to determine the types of maxim violations used by characters. The investigation concerns the kinds of maxim violations and the context of the situation in the movie. This study aims to analyze the types of maxim violations by using the theory of Grice (1975). This study applied the descriptive qualitative method in analyzing the data collected by some steps; the first are by watching the movie while reading the subtitle, then reading the script of the movie again and taking a note of the conversation that violated in the movie. The findings showed four types of maxim violations used by the characters. The study results showed that the types of maxim violations found in the movie are 24 data. The dominant maxim violation uttered by the characters in this movie is maxim quality. The finding shows that the most dominant maxim violation used by the character is a violation of maxim quality. The characters in the movie, when they make the conversation, each character sometimes answer it by giving untruth information or lies.